Combating Rx Drug Misuse: Incarcerated Women's Proactive and Reactive Policy Recommendations. (October 2019) - Owens, Jennifer Gatewood; Smirnova, Michelle
Given the rapid increase in prescription (Rx) drug misuse, overdose, and drug-related arrests, the purpose of this study is to identify strategies to combat Rx misuse from the perspective of former Rx drug misusers who are presently incarcerated. Using semi-structured interviews, we elicited such recommendations from 33 incarcerated women in the Midwest with histories of Rx drug misuse. The policy recommendations put forth by the women tended to be proactive rather than reactive and focused upon more vigilant surveillance and prevention efforts by medical professionals. While there was little mention of the criminal justice system or incarceration, women did also advocate for better treatment and rehabilitation options. Users affected by Rx misuse suggested more proactive approaches in dealing with Rx misuse that would ultimately shift drug control responsibilities from law enforcement to doctors.